How will countries compete for FDI in light of the new global tax environment? - Jeffrey Owens; Ruth Wamuyu (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The international tax framework has undergone several changes that present constraints to the use of tax incentives. This Perspective highlights these constraints and explores the potential opportunities, beyond the corporate tax realm, available to countries to attract foreign direct investment.
Keywords: 330